2016
DOI: 10.1007/s10048-015-0470-0
|View full text |Cite
|
Sign up to set email alerts
|

A novel heat shock protein alpha 8 (Hspa8) molecular network mediating responses to stress- and ethanol-related behaviors

Abstract: Genetic differences mediate individual differences in susceptibility and responses to stress and ethanol, although, the specific molecular pathways that control these responses are not fully understood. Heat shock protein alpha 8 (Hspa8) is a molecular chaperone and member of the heat shock protein family that plays an integral role in the stress response and that has been implicated as an ethanol-responsive gene. Therefore, we assessed its role in mediating responses to stress and ethanol across varying genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 88 publications
0
14
0
Order By: Relevance
“…In addition, we found some common proteins that were differentially expressed among the four comparison groups ( Figure S1A and Tables S1–4 ). These differential proteins included signaling protein high-mobility group protein B1 (HMGB1) a mediator of neurite degeneration through the identification of the pathological signaling pathway in AD [ 13 ]; molecular chaperones (heat shock cognate 71 kDa protein (HSP7C)), a molecular chaperone and a member of the heat shock protein family that plays an integral role in the stress response [ 14 ]; translationally controlled tumor protein (TCTP), which has critical roles in the defense against oxidative and thermal stresses [ 15 ] (shown in Table S1 ); endoplasmic reticulum (ER) stress-associated protein (protein disulfide-isomerase A6 (PDIA6)), a protein related to ER stress that plays a critical role in most biological processes [ 16 ]; oxidative stress-associated protein (D-3-phosphoglycerate dehydrogenase (SERA)), a protein involved in the metabolism and development of the central nervous system [ 17 ]; cytoskeleton-associated protein (peripherin (PERI)), a type III intermediate filament (IF) protein that plays a contributory role in motor neuron disease [ 18 , 19 ]; molecular chaperone (stress-induced-phosphoprotein 1 (STIP1)), a cochaperone intermediating Hsp70/Hsp90 exchange of client proteins and involved in prion protein-mediated neuronal signaling [ 20 ] (shown in Table S2 ); and cytoskeleton-associated protein (TPIS) (shown in Table S3 ). We found that two proteins, namely, isocitrate dehydrogenase [NADP] cytoplasmic (IDHC), which plays important roles in energy and biosynthesis metabolisms [ 21 ], and eukaryotic translation initiation factor 1b (EIF1B), an antiapoptotic protein that protects cells uniquely from Fas-induced apoptosis [ 22 ], were commonly changed in various concentrations of DAU-treated N2a/APP cells compared with the vehicle-treated N2a/APP cells (shown in Figure S1B and Table S8 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we found some common proteins that were differentially expressed among the four comparison groups ( Figure S1A and Tables S1–4 ). These differential proteins included signaling protein high-mobility group protein B1 (HMGB1) a mediator of neurite degeneration through the identification of the pathological signaling pathway in AD [ 13 ]; molecular chaperones (heat shock cognate 71 kDa protein (HSP7C)), a molecular chaperone and a member of the heat shock protein family that plays an integral role in the stress response [ 14 ]; translationally controlled tumor protein (TCTP), which has critical roles in the defense against oxidative and thermal stresses [ 15 ] (shown in Table S1 ); endoplasmic reticulum (ER) stress-associated protein (protein disulfide-isomerase A6 (PDIA6)), a protein related to ER stress that plays a critical role in most biological processes [ 16 ]; oxidative stress-associated protein (D-3-phosphoglycerate dehydrogenase (SERA)), a protein involved in the metabolism and development of the central nervous system [ 17 ]; cytoskeleton-associated protein (peripherin (PERI)), a type III intermediate filament (IF) protein that plays a contributory role in motor neuron disease [ 18 , 19 ]; molecular chaperone (stress-induced-phosphoprotein 1 (STIP1)), a cochaperone intermediating Hsp70/Hsp90 exchange of client proteins and involved in prion protein-mediated neuronal signaling [ 20 ] (shown in Table S2 ); and cytoskeleton-associated protein (TPIS) (shown in Table S3 ). We found that two proteins, namely, isocitrate dehydrogenase [NADP] cytoplasmic (IDHC), which plays important roles in energy and biosynthesis metabolisms [ 21 ], and eukaryotic translation initiation factor 1b (EIF1B), an antiapoptotic protein that protects cells uniquely from Fas-induced apoptosis [ 22 ], were commonly changed in various concentrations of DAU-treated N2a/APP cells compared with the vehicle-treated N2a/APP cells (shown in Figure S1B and Table S8 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have evaluated whether any of the specific phenotypes mapped back to the location of the differentially expressed genes in their respective group (Bice et al, 2010, 2006; Carhuatanta, Shea, Herman, & Jankord, 2014; Cook et al, 2015; Overall et al, 2009; Palmer, Lessov-Schlaggar, Ponder, McKinnon, & Phillips, 2006; Porcu et al, 2011; Urquhart et al, 2016). However, in the present study, only one phenotype mapped back to the location of a gene that was correlated with it: Cnot6l from the RSE vs. NOE group.…”
Section: Resultsmentioning
confidence: 99%
“…One such chronic illness linked to Cd14 and neuroinflammation is Alzheimer’s disease, which is heavily implicated with the hippocampus and can be detected in the hippocampal formation at an early stage before further symptoms arise [18, 19]. Perhaps more importantly, our previous studies have shown that gene expression in the hippocampus is particularly sensitive to the effects of acute ethanol (1.8 g/kg) [20, 21]. Others have also shown that acute ethanol (2.0 g/kg) produces brain region-specific changes in gene expression, including in the hippocampus [22].…”
Section: Introductionmentioning
confidence: 99%